Eco-Theological Pedagogy in Islamic Education: the Transformation of Teacher Professionalism at Madrasah Schools - Munawir Munawir; Achmad Yani; Imam Syafi'i (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
The environmental awareness crisis has caused an imbalance in the relationship between humans and nature. Increasing pollution, waste, and the loss of biodiversity are contributing to global warming. Islamic educational institutions must respond through eco-theological strategies. This study aims to describe strategies to develop the pedagogical competencies of Islamic education teachers in environmental stewardship at MAN 7 Jombang. Building on this development, the next objective is to describe the patterns of integrating eco-theology into the curriculum. This qualitative case study examines strategies for developing teachers’ competencies in environmental management and integrating these competencies into the curriculum. Primary data were collected from the school principal, the curriculum, and teachers at MAN 7 Jombang. The research findings indicate that the development of teachers’ pedagogical competencies is carried out in three stages: 1) teachers are tasked with creating eco-theology modules and converting them into lesson plans; 2) teaching eco-theology by integrating it into classroom instruction and projects that provide long-term contributions; 3) the pinnacle of competency is the “green madrasah,” involving institutions and the community to protect the environment. This pattern represents a paradigm shift in eco-theology, leading to the subjective analysis that eco-theology can be realized in character, behavior, and social and religious projects.